The determinants of exchange rate in Malaysia / Athirah Zainal - Zainal, Athirah (2016)
The study examines the determinants of real exchange rate in the recent years in Malaysia over the period of 1986 to 2016 using the Malaysia time series data. Following literature, it is identified the potential determinants of real exchange rate as current account balance, real interest rate and inflation rate. The result suggests that only current account balance have positive significant relationship and consistent with theory to influence the changes of exchange rate in Malaysia. The result further indicates that interest rate have positive relationship with exchange rate, consistent with theory but not significant to determine the exchange rate in Malaysia. The study also indicates that inflation rate have negative relationship with exchange rate, consistent with theory but not significant to determine the exchange rate in Malaysia.